On the norms of the means of spherical Fourier sums - Kuznetsova, O.I. (Труды Института прикладной математики и механики, 2015)
The spherical Fourier sums of a periodic functions in m variables, the strong means and the strong integral means of these sums for p ≥ 1 are considered. In contrast to the one-dimensional case treated by Hardy and Littlewood, for m ≥ 2 the norms of the corresponding operators in the space L∞ are not bounded. The sharp order of growth of these norms is found. The upper and lower bounds differ by a factor depending only on the dimension m. A sufficient condition on the function ensuring the uniform strong p-summability of its Fourier series is given.